Preventing metabolic-associated fatty liver disease with fermented cordyceps preparation: an electronic medical record based study - Zhou, Xiaozhou; Tian, Zijian; Li, Shaoyun; Jing, Ruifeng; Liu, Ziqing; Wu, Peng; Shao, Jian; Bai, Jie; Huang, Rong; Pan, Ying; Zhou, Kaixin (Frontiers in Medicine, 2025)
BackgroundMetabolic-associated fatty liver disease (MAFLD) is a prevalent chronic liver condition with significant health implications. Fermented Cordyceps Preparation (FCP) has shown promise in managing metabolic disorders, prompting interest in its potential for MAFLD prevention. There is, however, a lack of large-scale clinical evidence regarding its preventive efficacy and long-term safety.AimWe aimed to assess the preventive efficacy and safety of FCP, as regards combatting MAFLD.MethodsPropensity score matching was used to select 343 FCP users and 1372 non-users with metabolic syndrome, (MS) as recorded in EMR. These two groups were followed for 750 days, to track the incidence of MAFLD. The Kaplan Meier method was used to calculate the cumulative risk of MAFLD events in each subgroup. A Multiple linear regression model was used to compare the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), as between the two groups.ResultsCompared with non-users, FCP users were associated with a 26% decreased risk of MAFLD (hazard ratio 0.74, 95% confidence interval 0.56–0.97). During the follow-up, the changes in both ALT and AST, were insignificantly different between the two groups.ConclusionThese findings highlight the potential of FCP in MAFLD prevention and offer insight into its safety profile, suggesting avenues for further clinical validation and drug repurposing efforts.